VIDEO TUTORIAL IBADAH HAJI PADA SAUDARAKU UMRAH DAN HAJI BERBASIS WEB - Tisara Yanuastari; Jauharul Maknunah; Liduina Asih Primandari (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2023)
Umrah and Hajj in order to have the terms and harmonious rules that must be done perfectly. And to carry out the terms and the pillars of the pilgrims have to get lessons, known as umrah and hajj video tutorials. Video Umrah and Hajj is basically learning or provide information to prospective pilgrims about the manner of carrying out Umrah and Hajj.Many Umrah and Hajj guidelines presented in book form as the initial information to learn Umrah and Hajj, in addition, it can also look through the practice of video tutorials done by looking at the conditions that will be carried out in the course of Umrah and Hajj for example by looking ka'baah and menggenakan ihram clothes, but it is less efficient in order to improve the community in studying in detail the researchers made a video tutorial Umrah and Hajj web based program used in this website is HTML and PHP. The method used in this application is a collection of data that includes interviews, observation, literature and the development of applications that include design and video design, application development. The result is a built in video tutorial describes the pilgrimage from beginning to end and can help in learning procedures for Umrah and Hajj, with practical and easy to understand by the Umrah and Hajj pilgrims.